An approach to correlate experimental and theoretical thermal conductivity of MWNT/PMMA polymer composites. (11th September 2015) - Verma, M; Patidar, D; Sharma, K B; Saxena, N S
Abstract: In this paper an effort is made to correlate temperature dependent effective thermal conductivity measured by experimental method to theoretical results obtained from different models. MWNT/PMMA polymer nanocomposites were prepared by solution casting method, with different wt% of MWNT (0, 0.05, 0.1, 0.2, 0.3, 0.5, 1, 5, 10 wt%) dispersed in the PMMA matrix. The effective thermal conductivity from 30 °C to 110 °C is measured by Hot Disk Thermal Constant Analyser, based on transient plane source technique. Experimental study reveals that effective thermal conductivity increases with increasing concentration of MWNT in PMMA and increases exponentially at high temperatures for high (5, 10) wt% samples. This behavior of effective thermal conductivity is explained in terms of the interactions between polymer–MWNT and MWNT–MWNT. Consequently these results were found to be in agreement with theoretical models such as Series, Parallel, Lewis/Neilson and empirical formula. The discrepancy found in Lewis/Neilson model at high temperature for high wt% of MWNT in PMMA is due to some change in values of parameters incorporated in the model.